The hobbit - Potts, Stephen W., 1949- (Ipswich, Massachusetts : Salem Press, a division of EBSCO Information Services, Inc. : Grey House Publishing, 2016)
J.R.R. Tolkien's novel was met with international acclaim upon its publication in 1937, given its adventurous plot, elements of high fantasy, and lovable protagonist, Bilbo Baggins. This compilation of essays closely studies the classic staple of children's literature by examining some of its themes-such as maturation and overcoming greed-exploring the world of Middle-earth, and comparing/contrasting the text with its popular sequel, The Lord of the Rings.
The Portal to Middle-earth / Stephen W. Potts -- The Life of J.R.R. Tolkien / Stephen W. Potts -- J.R.R. Tolkien's world : literary, cultural, and historical influences on Middle-earth's subcreator / Kelly R. Orazi -- An unexpected success : the Hobbit and the critics / Alicia Fox-Lenz -- The riddles and the cup : medieval Germanic motifs in the Hobbit / Jason Fisher -- Bilbo Baggins, Harry Potter, and the fate of enchantment / John Rosegrant -- "Of gold and an alloy" : Tolkien, the Hobbit, and the northern heroic spirit / Hannah Parry -- "Witness those rings and roundelays" : The Hobbit as fairy-story / Jared Lobdell -- Fairy-stories that fueled the Hobbit / Kris Swank -- The poems of the Hobbit / Josh Brown -- A turning point in his career : the effect of the Hobbit on Middle-earth / Sara Waldorf -- The Hobbit : a mythopoeic need for adventure / Jelena Borojevic -- Growing up Tolkien : finding our way through Mirkwood / Kayla Shaw -- How to slay a dragon when you are only three feet tall / t
Includes bibliographical references (pages 229-233) and index.
Keywords: Tolkien, J. R. R. -- 1892-1973.; Tolkien, J. R. R. -- 1892-1973 -- Criticism and interpretation